COLLABORATIVE GOVERNACE DALAM MENGATASI KERUSAKAN DAERAH ALIRAN SUNGAI (DAS) BATANG KUANTAN TAHUN 2023 - Rawanda, Muhammad Martunus; Nasution, Hazqon Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The aim of this research is to determine and analyze the collaborative governance process in overcoming damage to the Batang Kuantan river basin. The condition of the Batang Kuantan River water is no longer suitable for use or is polluted, the color of the Kuantan River water is currently not clear (murky). This has resulted in the Kuantan River fish being greatly reduced. The destruction of river ecosystems and the threat of aquatic biota has resulted in the loss of livelihoods and those who work as fishermen and fish farmers. The theory used is the collaborative governance model proposed by Ansell & Gash, with a focus on four main dimensions, namely Face-to-Face Dialogue, Trust Building, Commitment to the Process, and Shared Understanding. The research method used is qualitative. The research results show that the government's collaborative process in dealing with damage to the Batang Kuantan Singingi watershed has been ongoing, but still faces several significant obstacles. There are weaknesses in the Commitment to the Process dimension which are shown by the absence of specific regulations. In the Shared Understanding dimension, obstacles were also found in the form of differences in perception and understanding between stakeholders regarding priorities for handling this problem. This research suggests that it is necessary to strengthen the commitment aspect in order to create a good mutual understanding. Keywords: Face-to-Face Dialogue, Trust Building, Commitment to the Process, dan Shared Understanding